Characteristics of Functional Cerorot with Pumpkin Flour Substitution (Cucurbita moschata) - Safitri, Baiq Idiya; -, Zainuri; Cicilia, Siska (Journal of Food and Agricultural Product, 2025)
Cerorot is a traditional food made from rice flour, brown sugar and coconut milk. The most dominant nutritional content is carbohydrates and very low vitamin content, especially vitamin A. This study used pumpkin flour as an effort to increase the nutritional value of cerorot. The purpose of this study was to examine the characteristics of cerorot made from rice flour and pumpkin flour. The ratio of rice flour and pumpkin flour in making cerorot (CL) with CL0 = 100%: 0%, CL1 = 85%: 15%, CL2 = 70%: 30%, CL3 = 55%: 45%, CL4 = 40%: 60%, and CL5 = 25%: 75%. The parameters observed were water content, ash content, antioxidant activity, beta-carotene, color, and taste. The concentration of pumpkin flour had a significantly different effect on all parameters. The ratio of 25% rice flour: 75% pumpkin flour was recommended as the best treatment that produced cerorot with characteristics of 41.31% water content; 4.35% ash content; 43.29% antioxidant activity; beta-carotene 40.27%, as well as color, taste, and aroma acceptable to panelists. Keywords: cerorot, pumpkin flour, rice flour